Optic nerve sheath diameter and its association with brain swelling in pediatric cerebral malaria: a retrospective study - Raees, Madiha Q.; Gushu, Montfort Benard; Taylor, Terrie E.; Seydel, Karl B.; Wynkoop, Hunter J.; O’Brien, Nicole F. (Frontiers in Pediatrics, 2024)
Introduction: Mortality in pediatric cerebral malaria (CM) in low-and-middle income countries (LMICs) is associated with brain swelling on magnetic resonance imaging (MRI); however, MRI is unavailable in most LMICs. Optic nerve sheath diameter (ONSD) measurement is an inexpensive method of detecting increased intracranial pressure (ICP) compared to the invasive opening pressure (OP). Our primary objective was to determine if increased ONSD correlated with brain swelling on MRI in pediatric CM. Our secondary objective was to determine if increased ONSD correlated with increased OP and/or poor neurological outcome in pediatric CM. We hypothesized that increased ONSD would correlate with brain swelling on MRI and increased OP and that ONSD would be higher in survivors with sequelae and non-survivors. Methods: We performed a retrospective chart review of children aged 0-12 years in Blantyre, Malawi from 2013-22 with CM as defined by the World Health Organization. Brain swelling on admission MRI was characterized by brain volume scores (BVS); severe swelling was scored as 7-8, mild-to-moderate as 4-6, normal as 3. Admission ONSD was measured via ultrasound; abnormal was defined as >4.5 mm in children >1 year and >4 mm in children <1 year. Favorable outcome was defined as a normal neurological exam on discharge in survivors. Primary and secondary objectives were evaluated using Spearman's correlation; demographics were compared using Chi square and Kruskall-Wallis (Stata, College Station, TX). Results: Median age of the 207 patient cohort was 50 months (IQR 35-75); 49% (n=102) were female. 73% (n=152) had a favorable outcome; 14% (n=30) died. Twenty-nine (14%) had a normal BVS, 134 (65%) had mild-to-moderate swelling, and 44 (21%) had severe swelling. ONSD was elevated in 86% (n=178) of patients, while 12% of patients had increased OP. There was a weakly positive correlation between BVS and ONSD (r=0.14, p=0.05). Median ONSD was not significantly different compared by discharge outcome (p=0.11) or by BVS (p=0.18). Conclusion: ONSD was not a reliable tool to correlate with BVS, neurological outcome, or OP in children with CM. Future studies to identify alternative methods of early identification of CM patients at highest risk for morbidity and mortality are urgently needed.